(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
The Miocene-Pliocene sedimentary succession of southwestern Piedmont Tertiary Basin, outcropping near Mondovì, is here briefly described. Planktonic and benthic foraminifers are analyzed with the aim to date the sediments and to investigate their paleoenvironmental conditions. In the southern and western outcrops, marls and silty marls from the N7 Zone (Late Burdigalian) to the N10 Zone (Serravallian) seem to testify a continue sedimentation at an upper epibathyal depth. A gap could separate these sediments from the overlying silty marls, attributable to the N16 Zone (Tortonian) of outer neritic or upper epibathyal zone. In the northeastern outcrops, clayey and sandy marls seem to be sedimented during the Early Pliocene in the outer neritic or upper epibathyal zone. Coarser sediments (silts, silty sands, sandy gravels) yield outer neritic to inner neritic foraminiferal associations, probably Pliocene in age. They might be more recent than the Early Pliocene marls or may represent heteropic facies.